Encoding of emotion-paired spatial stimuli in the rodent hippocampus - Nalloor, Rebecca; Bunting, Kristopher M.; Vazdarjanova, Almira (Frontiers in Behavioral Neuroscience, 2012)
Rats can acquire the cognitive component of CS-US associations between sensory and aversive stimuli without a functional basolateral amygdala. Thus, other brain regions should support such associations. Some septal/dorsal CA1 (dCA1) neurons respond to both spatial stimuli and footshock, suggesting that dCA1 could be one such region. We report that, in both dorsal and ventral hippocampus, different neuronal ensembles express immediate-early genes when a place is experienced alone vs. when it is associated with foot shock. We assessed changes in the size and overlap of hippocampal neuronal ensembles activated by two behavioral events using a cellular imaging method, Arc/Homer1a catFISH. The control group (A-A) experienced the same place twice, while the experimental group (A-CFC) received the same training plus two foot shocks during the second event. During fear conditioning, A-CFC, compared to A-A, rats had a smaller ensemble size in dCA3, dCA1 and vCA3, but not vCA1. Additionally, A-CFC rats had a lower overlap score in dCA1 and vCA3. Locomotion did not correlate with ensemble size. Importantly, foot shocks delivered in a training paradigm that prevents establishing shock-context associations, did not induce significant Arc expression, rejecting the possibility that the observed changes in ensemble size and composition simply reflect experiencing a foot shock. Combined with data that Arc is necessary for lasting synaptic plasticity and long-term memory, the data suggests that Arc/H1a+ hippocampal neuronal ensembles encode aspects of fear conditioning beyond space and time. Rats, like humans, may use the hippocampus to create integrated episodic-like memory during fear conditioning.